Natural adsorbent made from eggshells for removal of chromium (VI) in water - Abdul Latif, Amirul Faiz; Loh, Siew Yee; Muhamad, Mimi Suliza; Lee, Te Chuan; Basri, Hatijah (2022)
Substantial utilization of heavy metals in various industrial processes nowadays had cause heavy metal pollutions in the water. Hexavalent chromium, Cr (VI), is one of the heavy metals which has been extensively used in alloy pigment production and surface treatment. The present work reports natural adsorbent synthesis made from eggshell to reduce Cr (VI) in water. The eggshell adsorbents were prepared by several steps that include boiling, drying, calcination at 900 °C, grinding, pH adjustment, precipitation, and filtration. XRD results displayed a highly crystalline hydroxyapatite (HAp) peak that was successfully synthesized. FESEM analysis showed the morphology of the powder that was agglomerate with irregular cloud-like shapes, while EDS results presented the elements in the eggshell powders that include calcium (Ca), phosphorus (P), and oxygen (O). FTIR analysis revealed the presence of hydroxyl group (OH-) that contribute to the adsorption process. The adsorption experiment demonstrates the highest Cr (VI) removal and adsorption capacity of 70% and 285.71 mg/g, respectively, was attained by 6 g adsorbent dosage within 1 hour. Kinetic studies of the adsorption process were best described by the pseudo-second-order model and Langmuir isotherm model with a high correlation coefficient of 0.98. This work's findings suggested that eggshells are potential natural adsorbent to reduce heavy metal pollutions, specifically Cr(VI) in water.